Prevalence of burnout among medial students in Universiti Sultan Zainal Abidin and its relationship with emotional intelligence - Daud, Norwati (2020)
The prevalence of burnout among medical students is shown to be high across many countries. Burnout is associated with stress and mental health issues among medical students. Many factors are associated with burnout among medical students. Previous studies also showed that emotional intelligence was protective against burnout. The study aimed to determine the prevalence of burnout among medical students in Universiti Sultan Zainal Abidin (UniSZA) and its association with emotional intelligence and other demographic and academic factors. In total, there were 200 medical students at the Faculty of Medicine UniSZA invited to participate in the study. The students were from year one to year five selected using stratified random sampling. An online Google Form questionnaire consisting of demographic data, a Malay translation of the Copenhagen Burnout Inventory (CBI-M) and the USM Emotional intelligence inventory (USMEQ-i) was distributed using WhatsApp application. Demographic data included gender, race, year of study and self -reported entry CGPA. The outcome was in the form of burnout which was categorised into significant and non-significant burnout based on the CBI-M score. Each factor was analysed using a Chi-Square test to determine its association with burnout. Entry CGPA and EI were analysed using an independent t -test. 182 medical students responded. The response was 91.0%. The distribution of medical students responded was according to the current proportion by gender, race and year of study. The percentage of students categorised as having significant burnout was 36.8% (95% CI 29.8; 44.3). The mean (SD) for EI score was 2.85 (0.52). There was a negative correlation between EI and burnout (r=-0.395) and it was statistically significant (P< 0.001). EI was significantly associated with burnout while gender, race, year of study and entry CGPA were all not significantly associated with burnout. As a conclusion, the prevalence of burnout among medical students in UniSZA was at a moderate percentage compared to that of other countries. EI was found to be protective against burnout. Measures need to be taken to prevent burnout among medical students and may be incorporated into the medical curriculum. EI may be considered as one skill to be developed to reduce burnout.